A Study on the Birds of Small Islands off the Coast of Cebu Island, Philippines - Pagunutalan, Lisa Marie J.; Jakosalem, Philip Godfrey C.; Pedegrosa, Marisol G.; Catacutan, Mery Jean G. (Silliman Journal, 2022)
The bird composition of the small islands of Carnaza, Camotes (Poro and San Francisco), Gato, Pescador and Sumilon in Central Visayas was studied by deliberate search, mist-netting, and point counting. A total of 67 species of birds were recorded on all five islands. Forty-three species observed were breeding residents, 14 were migratory, and 2 were either residents or migrants; 8 species were Philippine endemics. The presence of Black-crowned Night-Heron Nycticorax nycticorax and the Caspian Tern Hydroprogne caspia provided new records for Gato Island. Glossy Starling Aplonis panayensis and the Pied Triller Lalage nigra were the most frequently netted birds. The island of Camotes, the largest of the five islands visited, had the highest number of species recorded followed by Carnaza, Sumilon, Pescador, and Gato Island. The study did not record any subspecies or species endemic to Cebu. Hunting of birds and large species of mammals mainly for the pet trade, food, and sports is still practiced. Native species of tree and mangroves are illegally cut mainly for firewood, and household use. The conservation efforts on these islands are concentrated on marine resources with less attention to terrestrial wildlife.